From Threat to Risk: Changing Rationales and Practices of Secrecy. (4th May 2022) - Heide, Marlen
Abstract: This article explores how risk rationales affect and alter national security secrecy. While the transformation of defense and security policy has been widely discussed by security theorists, transparency scholars have not yet considered the notion of risk in their conceptualizations of national security secrecy. This article draws on security studies literature to outline the divergences between conventional and risk-based security. The empirical section investigates how the difference between both rationales manifests in secrecy practices by investigating conventional and risk-based classification frameworks (in Germany compared to the United Kingdom). In a risk security setting, information is increasingly seen as an asset and therefore subject to proactive management and exploitation. This requires a shift from a bureaucratic risk aversion in classification practices toward sharing, exploitation, and availability of information. Further, information governance is no longer about the separation between sensitive and nonsensitive information, but instead a comprehensive evaluation of all government assets for risks. These shifts ultimately change conventional understandings of secrecy as an "exemption" and a "necessity, " impelling new debates about the legitimacy of secrecy practices.